Prevalence of colorectal symptoms and anal incontinence in patients with pelvic organ prolapse attended at an outpatient urogynecology service - Marco Arellano; Fernanda Santis-Moya; Andrea Maluenda; Alejandro Pattillo; Bernardita Blümel; Dominga Pohlhammer; Silvana Gonzalez; Javier Pizarro-Berdichevsky (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: To analyze data of patients with symptomatic pelvic organ prolapse evaluated with PFDI20 and its subscales to report the prevalence of lower gastrointestinal symptoms and anal incontinence in the population of a public hospital and analyze its impact on quality of life. Methods: Cross-sectional study of patients with symptomatic POP. Patients were evaluated with demographic data, POP-Q, pelvic floor ultrasonography, urological parameters, and pelvic floor symptoms (PFDI-20), and quality of life (P-QoL) surveys. Patients were classified as CRADI-8 "positive" for colorectal symptoms, with responses "moderate" in at least 3 and/or "severe" in at least 2 of the items in the CRADI-8 questionnaires. Results: One hundred thirteen patients were included. 42.5% (48) were considered positive for colorectal symptoms on CRADI-8. 53.4% presented anal incontinence. No significant differences were found in sociodemographic variables, POP-Q stage, ultrasound parameters, or urological parameters. Positive patients had a significantly worse result in PFDI-20, POPDI (48 vs 28; p<0.001), UDI6 (51 vs 24; p<0.001), and in the areas of social limitation (44.4 vs 22.2; p = 0.045), sleep- energy (61.5 vs 44.4; p = 0.08), and severity (56.8 vs 43.7, p=0.015) according to P-QoL. Conclusion: Moderate or severe colorectal symptoms are seen in 40% of patients with symptomatic POP in our unit. Full evaluation of pelvic floor dysfunction symptoms should be performed routinely in urogynecology units. (FONIS SA12I2I53 - NCT02113969).